Continuity of care as a predictor of ongoing frequent attendance in primary care: a retrospective cohort study. Issue 5 (December 2020) - McDermott, Adam; Sanderson, Emily; Metcalfe, Christopher; Barnes, Rebecca; Thomas, Clare; Cramer, Helen; Kessler, David
No abstract available